ADVANCEMENTS IN DENTAL IMPLANT PLANNING THROUGH COMPUTED TOMOGRAPHY - Alves, Leonardo Dornelas (Revista Sistemática, 2024)
The planning of dental implants plays a crucial role in determining the success of dental treatments. Recent advancements in technologies, particularly computed tomography (CT), have significantly transformed this practice by allowing precise three-dimensional evaluations of oral anatomy and bone quality. This enhanced capability provides detailed insights that facilitate the optimal positioning of implants while minimizing surgical risks. Studies highlight the effectiveness of using customized surgical guides based on CT data, which not only improve the accuracy of dental interventions but also enhance patient experiences by promoting quicker recovery and ensuring implant stability. The shift towards digital techniques in surgical planning underscores the importance of tailoring approaches to the individual characteristics of each patient, thereby improving overall outcomes. Research supports the use of three-dimensional model-based surgical guides in conjunction with CT imaging, which leads to less invasive procedures and more predictable results. As a result, these technologies represent a significant advancement in dental implant procedures, elevating the quality of care and expanding clinical possibilities. The integration of imaging technologies and meticulous preoperative planning is essential in modern dentistry, and ongoing technological advancements promise to further enhance these methods. By continuing to incorporate these innovations into clinical routines, dental professionals can achieve superior results for their patients, marking a progressive shift in dental implantology.